Effects of timeliness and quality of tractor-hire services on smallholder farmers’ technical, allocative, and economic efficiencies: Evidence from Botswana - Tebogo Mokumako; Samuel Kwesi Ndzebah Dadzie; Henry Nana De-Graft Acquah; Alexander Tetteh Kwasi Nuer; Emmanuel Wisgtos Inkoom; Michael Robert Nkuba (Scientific African)
Smallholder farmers contribute to aggregate food production. However, their yields are low in Botswana, despite government subsidies for tractor-hire services and seeds to improve productivity and food security. In semi-arid areas, the onset of rains is variable, making access to inputs around the onset of rains critical for smallholders’ crop productivity. The study aimed to assess the effects of farmers’ timely access to tractor services on their efficiency. This study examined smallholder arable crop farmers’ technical, allocative, and economic efficiencies. The household survey gathered data on farmer characteristics, socio-economic, and production. Data was collected from 470 smallholder arable crop farmers in Central District, Botswana. The Stochastic Frontier Approach (SFA) was used to analyze the efficiencies, and the Tobit regressions were used to determine the factors influencing the efficiencies. The results show that poor quality and delays in farmers’ access to tractor-hire services negatively affect technical and economic efficiencies. Smallholders had a mean technical efficiency score of 44 %, an allocative efficiency score of 6.6 %, and an economic efficiency score of 2.9 %. The input subsidy program positively influences farmers’ productivity. Agricultural input policies should take serious consideration of quality and timeliness of smallholders’ access to inputs and services in a bid to increase their production efficiencies.